Mechanical structures for electronic equipment. Thermal management for cabinets in accordance with IEC 60297 and IEC 60917 series. Design guide. Interface dimension and provision for thermoelectrical cooling systems (Peltier effect) Part 1, (31st January 2010) - British Standards Institution,
No abstract available